Evaluasi Penggunaan Sediaan Farmasi Intravena Untuk Penyakit Infeksi Pada Salah Satu Rumah Sakit Swasta Di Kota Bandung - Surahman, Emma; Mandalas, Esther; Kardinah, Endah Ismu (Majalah Ilmu Kefarmasian, 2008)
An usage evaluation of intravenous pharmaceutical dosage form for infectious dis-eases at one of the private hospitals in Bandung by retrospective method on October to December 2005 had been done based on the rationality of drug used according to the certain criteria. The result of the evaluation from 1170 prescriptions found that the combination of two or more drugs was 7.78%, no drug dose improper, no duplication of drug used, nor interaction with another drugs were found. The preparation of intravenous pharmaceutical dosage form had been well done, but the aseptic tech-nique still less of attention.